Noise pollution and its environmental perception in the educational community of cercado de Tacna, 2019 - Mamani Valdez, Antuanne Mariela (2020)
This research aims to assess the environmental noise in the surroundings of the educational institutions of the Tacna fence and the social perception that the educational community has about noise, for this it was compared with the national regulations (Environmental Quality Standard) and the international regulations (Values proposed by the World Health Organization), in the methodology: monitoring were carried out in 13 educational institutions , during school hours, between the months of May, June and July. Subsequently, 265 surveys were conducted as an instrument for assessing social perception, to determine the educational community's knowledge of noise, the consequences on their quality of life, etc. Subsequently, an environmental noise map was developed. As a result, the average values obtained ranged from 43.18 dBA to 69.25 dBA. In conclusion, no educational institution complies with international standards (35 dBA, according to WHO), five educational institutions exceed 50 dBA (ECA established for special protection zones), and people who are constantly exposed to high levels of noise present problems in class development, affecting their quality of life and health, such as constant headaches, irritation, stress and lack of concentration.